PENERAPAN RELAKSASI BENSON DAN MUROTTAL SURAH AR-RAHMAN TERHADAP PENURUNAN NYERI PASIEN GASTRITIS DI RSUD MAMUJU - Salaka, Syafruddin Ali; Hasir, Hasir; Yusuf, Sri Reski Auliah (STIKES Borneo Cendekia Medika, 2024)
Background: Gastritis is inflammation of the stomach wall which is characterized by heartburn, nausea and vomiting accompanied by decreased appetite. Gastritis is often called stomach ulcers or heartburn. If left untreated, it will cause stomach bleeding which can lead to death. The most common symptom of gastritis is heartburn. Pain management can be done pharmacologically and non-pharmacologically. Research method: using a descriptive case study method by applying a combination of Benson and Murottal Surah Ar-Rahman relaxation techniques to three patients as respondents who experienced nursing problems with discomfort and pain for 3 days with a duration of 10 minutes. Measurements were carried out before and after the intervention using the Numeric Rating Scale (NRS). Results: there was a decrease in the pain scale on the second and third days after the combination of the Benson and Murottal Surah Ar-Rahman relaxation techniques. Conclusion: Application of a combination of Benson relaxation techniques and murottal Al-Quran Surah Ar-rahman can reduce the pain scale in gastritis patients in the Mawar Room at Mamuju District Hospital